Rendimento e composição química do filé de prochilodus lineatus do rio mogi guaçu, Brasil - Machado, M. F. R. [UNESP]; Foresti, F. [UNESP] (SciELO Espana/Repisalud, 2009)
The curimbata constitutes species of fish of wide distribution in the Neotropical area and high economic value. This work focused to evaluate processing yield and the chemical composition of the fillet in the male and female migratories and residents stocks of Prochilodus lineatus. The using the plotting was completely randomized by 4x2 factorial scheme, having as factors four stocks (one resident and three migratories) and two genders (male and female) with thirty replicates, considering each fish as an experimental unit. Each individual was submitted to the manual filleted and determination of the corporal composition (texts of moisture, crude protein, lipids, ashes and energy). They following parameters of yield had been evaluated (%): visceral entire fish (RPIE %); yield of boneless fillet (RFILE %) and processing yield of fillet with bone (RFILEC %). There was a significant difference (p<0.05) between the stocks and the studied samples. The biggest yield of boneless fillet were observed for the fish of the migrator stock I (45.77%). Males and females of the migrator stock I presented biggest fillet yield (46.79% and 43.93%, respectively), while the migrator III presented smaller yield (37.29% for males and 38.44% for females). The migratories stocks I, II and III presented values significantly smaller (p<0.05) of lipids level (0.98%; 2.01% and 1.97%, respectively) and an increase in the content of corporal protein in relation to the resident stock. It concluded that the male weighing 591g on average, belonging of the stock migrator I (captured in December), presented better thread yield and the stocks migratories are fish that has low fat tenor and high protein tenor.
Processing yield and chemical composition of the Prochilodus lineatus from mogi guaçu river, Brazil
Keywords: Corporal composition; Filleted; Processing of fish; Prochilodus lineatus